Language Proficiency in Standard and Non-Standard Language Among Students of The Faculty of Economics, State University of Medan - Lubis, Fitriani; Nathanael, Kalfani; Samosir, Nus Dencoco; Regar, Santa Gresella Br; Maharani, Wasima Agita; Khairunnisha, Zainka (EDUCTUM: Journal Research, 2023)
The use of proper and standard Indonesian language in the current modern era has been increasingly eroded. This can be observed from the proliferation of slang or foreign languages, especially among young people. The purpose of this research is to determine the proficiency of using proper Indonesian language among young people, particularly students in the Faculty of Economics at Universitas Negeri Medan. The Data Analysis Technique used is qualitative data analysis conducted in accordance with a phenomenological approach. Through purposive sampling, the research sample consists of 10 students from the Faculty of Economics at Universitas Negeri Medan who use both proper and non-standard language in Indonesian. This sample aims to depict the characteristics of the research population. The research findings conclude that the existence of the Indonesian language faces significant challenges in the modern era. The emergence of non-standard language, influenced by assimilation with foreign languages and media influence, has shifted the understanding and usage of correct Indonesian language.